Equicontinuous Factors, Proximality and Ellis Semigroup for Delone Sets - Aujogue-, J (Springer Basel, 2015)
We discuss the application of various concepts from the theory of topological dynamical systems to Delone sets and tilings. In particular, we consider the maximal equicontinuous factor of a Delone dynamical system, the proximality relation and the enveloping semigroup of such systems. © 2015 Springer Basel.